Understanding viewer support in video game streaming: key insights into donation drivers - Serrano-Malebrán, Jorge; Campos-Núñez, Franco; Veneros-Alquinta, Diana; Meza-Espinoza, Neil; Alfaro-Tirado, Ignacio; Cucho-Solano, Juan (Frontiers in Communication, 2025)
The rise of video game streaming (VGS) platforms has transformed how audiences’ engagement with content and support creators through voluntary donations. This study examines the psychological and relational factors that influence donation intentions among Chilean Millennials and Centennials, drawing on the Stimulus–Organism–Response (S–O–R) theoretical framework. We conceptualize parasocial relationships and social presence as social stimuli that shape affective and cognitive organismic states—enjoyment, loyalty, trust, and satisfaction—which, in turn, influence the intention to donate. Data were collected via an online survey (N = 401) and analyzed using partial least squares structural equation modeling (PLS-SEM). The findings reveal that parasocial relationships significantly influence all four organismic states, while social presence impacts enjoyment, loyalty, and satisfaction but not trust. Among the organismic variables, only loyalty and satisfaction significantly predicted donation intentions. The model explains 33.7% of the variance in donation behavior. These results suggest that affective connection and relational satisfaction are stronger drivers of financial support than enjoyment or trust. This study contributes to the literature by applying and validating the S–O–R model in a Latin American context and highlighting the central role of relational engagement in technology-mediated donation behavior on VGS platforms.